Description Of Head Lice (Pediculus capitis) Infection Of Primary School Age Children In Elementary School Negeri 40, Salero District, Central Ternate District, Ternate City, 2022 - Tomia, Amalan; Tuharea, Rosmila (International Journal of Science, Technology & Management, 2024)
Head lice are the cause of the ectoparasitic disease pediculosis capitis. Both adults and children in school can have head lice. A public elementary school (SDN) 40 in Salero Village, Ternate City is utilized to illustrate how Pediculus capitis might spread. The purpose of this study is to characterize head lice infections caused by Pediculosis capitis in elementary school-aged children and to identify the risk factors that contribute to the spread of this infestation. This study uses a descriptive, analytical, correlative research design. The children in grades 4, 5, and 6 of SDN 40 comprised the study's population. The process of sampling involved tracking head lice infections according to factors such as age, gender, infection location, itching in the head, hair type, length, and frequency of hair washing r with Pediculus capitis infection (p-value = 0.001 and OR 0.102-0.570); long hair with Pediculus capitis infection (value = 0.000 and OR 101-0.569); hair washing interval with Pediculus capitis infection (p-value = 0.000 and OR 0.019-0.415) and use of combs together with Pediculus capitis infection (p-value = 0.001 and OR 00.141-0.789). Hair type did not have a significant relationship with Pediculus capitis infection with a p-value = 0.852 and OR 0.477-2.505.